Redescription of Verrucoentomon montanum new status (=Acerella montana Martynova) (Protura: Acerentomidae, Nipponentominae) - Shrubovych, Julia (Zootaxa, 2011)
E. F. Martynova (1970) described two species of Protura from the Tian-Shan Mountains of Kyrgyzstan: Hesperentomon tianschanicum and Acerella montana. The descriptions are now outdated due to progress in proturan taxonomy in the last three decades, and the systematic position of A. montana is unclear. I redescribe A. montana based on the holotype female and another specimen mounted on the same slide. This slide is preserved in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg, Russia. The paratypes were not marked. I thank the head curator of Zoological Institute RAS, Dr. V.A. Krivokhatsky, Dr. V. Kuznetsova (St. Petersburg) and Dr. A. Nadachovska (Krakow) for their kindness and help. This work was supported by grant NN303 0683 34 from the Ministry of Science and Higher Education, Poland.